Nutritional Deficiencies in Pregnancy after Surgery for Morbid Obesity - Alexandrou, Andreas; Tzikos, George; Chatzi, Sofia; Augoulea, Areti; Angelou, Anastasios; Michalinos, Adamantios; Lambrinoudaki, Irene (Journal of Digestive Disorders And Diagnosis, 2017)
Objectives: The rate of morbid obesity among women of reproductive age continues to rise worldwide. Surgical treatment remains the most effective mean to face it. Anatomical, physiological and nutritional modifications lead to several challenges for pregnancy after bariatric procedures. In spite of routine supplementation after bariatric surgery, vitamin and mineral deficiency frequently appear in bariatric pregnancies. The aim of this review is to summarize the existing data on the prevalence and management of nutritional deficiencies in pregnancy after bariatric surgery. Methodology: A comprehensive search of Pubmed Database was conducted for English-language studies using a list of key words. Results: The most common post-operative deficiencies in pregnancy include iron, vitamin B12, folate, vitamin D and magnesium deficiency. Less common are selenium, vitamin A, vitamin B6 and vitamin C deficiency. Finally, copper, vitamin K, vitamin B1, vitamin E and albumin deficiencies are considered to be relatively rare. Conclusions: Pregnancy after bariatric surgery has been proven to be safe for both the mother and the fetus. However, there is still the risk of significant nutritional deficiencies with adverse effects on pregnancy and lactation. As a result, a thorough customized nutritional assessment is mandatory for every woman in reproductive age who has undergone a bariatric operation, with strict regular follow-up during pregnancy and lactation.
Keywords: bariatric surgery; morbid obesity; nutrition; pregnancy; vitamin deficiency